Clinical Reasoning in the Ward Setting: A Rapid Response Scenario for Residents and Attendings - Megan Ohmer (Association of American Medical Colleges, 2019)
Introduction There is a need for educational resources supporting the practice and assessment of the complex processes of clinical reasoning in the inpatient setting along a continuum of physician experience levels. Methods Using participatory design, we created a scenario-based simulation integrating diagnostic ambiguity, contextual factors, and rising patient acuity to increase complexity. Resources include an open-ended written exercise and think-aloud reflection protocol to elicit diagnostic and management reasoning and reflection on that reasoning. Descriptive statistics were used to analyze the initial implementation evaluation results. Results Twenty physicians from multiple training stages and specialties (interns, residents, attendings, family physicians, internists, surgeons) underwent the simulated scenario. Participants engaged in clinical reasoning processes consistent with the design, considering a total of 19 differential diagnoses. Ten participants provided the correct leading diagnosis, tension pneumothorax, with an additional eight providing pneumothorax and all participants offering relevant supporting evidence. There was also good evidence of management reasoning, with all participants either performing an intervention or calling for assistance and reflecting on management plans in the think-aloud. The scenario was a reasonable approximation of clinical practice, with a mean authenticity rating of 4.15 out of 5. Finally, the scenario presented adequate challenge, with interns and residents rating it as only slightly more challenging (means of 7.83 and 7.17, respectively) than attendings (mean of 6.63 out of 10). Discussion Despite the challenges of scenario complexity, evaluation results indicate that this resource supports the observation and analysis of diagnostic and management reasoning of diverse specialties from interns through attendings.